The Effect of Environmental Quality and Gender Inequality on Human Well-Being in Indonesia during Pandemic Covid-19 - Shanty Oktavilia; Andryan Setyadharma; Indah Fajarini Sri Wahyuningrum; Tania Wicaksana Yuneldi (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2022)
This study examines the impact of environmental quality and gender equality on human welfare in Indonesia from 2015-2020, using a panel database of 33 provinces. The results of the model selection testing with the Chow test and the Hausman test recommend regression analysis using the Fix Effect Model (FEM). This study resulted in the finding that there is a unidirectional and significant relationship between gender equality and human well-being. That means that gender inequality has the opposite effect. The second finding is that statistically, there is a positive relationship between environmental quality and human welfare in the case of provinces in Indonesia. The estimation results show that economic growth has a positive and significant relationship with human well-being in Indonesia. This study indicates that human well-being in Indonesia before and during the Covid-19 pandemic shows differences. The novelty of this study is to analyze the effect of gender equality and environmental quality indicators in influencing human welfare. In addition, this research also accommodates the Covid-19 pandemic period in an empirical model.